The effect of maize silage type on the performances and methane emission of dairy cattle. Issue 5 (21st November 2016) - De Boever, J. L.; Goossens, K.; Peiren, N.; Swanckaert, J.; Ampe, B.; Reheul, D.; De Brabander, D. L.; De Campeneere, S.; Vandaele, L.
Summary: To examine whether type of maize silage is important for milk production performances, maize silage LG30224 (LG) was compared with Falkone (FA), the latter having a 4.0% points lower rumen NDF digestibility and 19 g/kg dry matter (DM) more starch. To bridge the lower energy content of FA, a third treatment was involved by adding maize meal (MM) in a ratio of 92/8 on DM (FA+MM). Maize and grass silage were fed ad libitum in a ratio of 65/35 on DM basis. Concentrates were supplemented individually to meet energy and protein requirements. The experiment was set up as a Latin square with three groups of nine Holstein cows during three periods of 3 weeks. In the last 2 weeks of each period, DM intake (DMI) and milk performances were measured. Each group included one cannulated cow to study effects on rumen fermentation. During the last 4 days of each period, two cows from each group were placed in gas exchange chambers to measure nutrient digestibility and methane production. Total DMI was higher (p < 0.05) for FA+MM (20.8 kg/day) than for FA (20.3 kg/day), while DMI for LG was intermediate (20.6 kg/day). Treatment did not affect milk production nor composition, whereas fat–protein‐corrected milk was higher for LG (30.5 kg/day) and FA+MM (30.3 kg/day) than for FA (29.9 kg/day). The ration did not affect pH nor volatile fatty acid composition in the rumen. Further, total tract digestibility of OM, crude protein, NDF and starch did not differ among treatments. The ration with LG gave higher methane production per day and per kg NDF intake than both rations with FA, but the difference was not significant when expressed per kg DMI or FPCM. Thus, maize silage type is of little importance for milk production if energy and physical structure requirements are met.